The Communication of Customer Service Officers To International Passengers: A Study at I Gusti Ngurah Rai International Airport - Ferdian Andika Putra; Gallis Nawang Ginusti (Jurnal Manajemen Dirgantara, 2026)
Effective communication is a crucial element in airport services, yet the complexity of interactions with passengers from diverse backgrounds, especially foreign nationals, often presents significant challenges. This research examines the communication obstacles and barriers encountered by customer service officers when interacting with passengers, particularly foreign passengers, at I Gusti Ngurah Rai International Airport, Bali. A quantitative approach was employed with a descriptive research method. Data was collected through questionnaires administered to 75 customer service officers. Data analysis was performed to identify the descriptive statistics of the officers' responses. The results indicate that officers possess a good level of readiness and adaptability in communication. The most potential obstacle identified arises from officers' inadequate practical experience, especially in dealing with the complexities of interacting with foreign passengers. Meanwhile, the most prominent communication barriers are not solely linguistic in nature; they also encompass interrelated psychological, physical, and sociocultural aspects. The barriers are evidenced by a lack of confidence in using the language and an elevated cognitive load when processing or translating information, followed by physical and environmental factors, including passengers’ physical conditions, the physical distance, and the presence of crowds, as well as socio-cultural factors, such as stereotypes and value differences, have been shown to play a very significant role. These indicate the necessity to prioritize the cultivation of practical skills, self-assurance and cultural awareness, rather than merely enhancing language competence. Keywords: Intercultural Communication, Obstacles, Barriers, Customer Service, International Airport